Implementation of Cooperative Learning Model Types of Survey, Question, Read, Recite, Review(SQ3R) With Chain Card Media to Increase Students Creativity And Learning Outcome in Social Class Grade X - Santyo, Jonatan Tegar Tri; Agung S, Leo; Pelu, Musa (PAEDAGOGIA, 2021)
The purpose of this study to increase the creativity and students’ academic quality of students’ X IPS 1 at SMA Negeri 2 Sukoharjo through the use of cooperative learning SQ3R type with chain card media.  This research is classroom action research. Data sources come from informants, documents, and observation, Data collection technique is observation, interview, and test. Data analysis with qualitative and quantitative. Data were analyzed by comparing the shading result from the acquisition of test scores in each cycle. The result of the study show the following. First, the implementation of cooperative learning SQ3R type with  chain card media  has an increse students creativity to 100 percent from Cycle one to cycle two and has an increase  students learning outcomes to 65 percent become 77 percent from cycle one to cycle two.